Association between roxadustat use and suppression of thyroid function: a systematic review and meta-analysis - Yuki Nakano; Satoru Mitsuboshi; Kazuhiro Tada; Kosuke Masutani (BMC, 2024)
Abstract Background Based on several case reports and observational studies, there is a growing concern regarding the potential association between roxadustat, a hypoxia-inducible factor prolyl-hydroxylase inhibitor, and suppression of thyroid function. In this systematic review and meta-analysis (PROSPERO: CRD42023471516), we aimed to evaluate the relationship between roxadustat use and suppression of thyroid function. Methods We conducted a comprehensive search of MEDLINE via PubMed, ClinicalTrials.gov, and the Cochrane Central Register of Controlled Trials databases using the search term "roxadustat" to identify all relevant studies. The study population comprised adults with renal anemia who participated in a randomized controlled trial or observational study, with roxadustat as the intervention and a placebo or erythropoiesis-stimulating agent (ESA) as the comparator. The primary outcome was suppression of thyroid function and the secondary outcome was hypothyroidism. A meta-analysis was conducted using the DerSimonian-Laird random effects model based on the size of the intention-to-treat population, and the odds ratio (OR) and 95% confidence interval (CI) were calculated. Two reviewers independently screened the articles, extracted data, and assessed studies using the ROBINS-I tool. Results Of the six studies eligible for inclusion, a meta-analysis was performed using data from two observational studies comparing roxadustat and ESA. The meta-analysis showed that the incidence of suppression of thyroid function was significantly higher with roxadustat use than with ESA use (OR: 6.45; 95% CI: 3.39-12.27; I 2 = 12%). Compared with ESA, roxadustat seemed to potentially increase the risk for suppression of thyroid function in patients with renal anemia. Conclusions Our findings highlighted the importance of monitoring thyroid function in patients treated with roxadustat. The results of this review may enhance the safety of using roxadustat to treat renal anemia through advance recognition of the risk for suppression of thyroid function.